Evangelizing Lebanon : Baptists, Missions, and the Question of Cultures - Trexler, Melanie, 1982- (Book collections on Project MUSE., 2016)
In 1893, Said Jureidini, an Arabic-speaking Christian from the Ottoman Empire, experienced an evangelical conversion while attending the Chicago World's Fair. Two years later he founded the first Baptist church in modern-day Lebanon. For financial support, he aligned his fledgling church with American Landmark Baptists and, later, Southern Baptists. By doing so, Jureidini linked the fate of Baptists in Lebanon with those in the United States. In Evangelizing Lebanon, Melanie E. Trexler explores the complex, reflexive relationship between Baptist missionaries from the States and Baptists in Lebanon. Trexler pays close attention to the contexts surrounding the relationships, the consequences, and the theologies inherent to missionary praxis, carefully profiling the perspectives of both the missionaries and the Lebanese Baptists.